The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12875-020-01212-y
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners’ perceptions of their practice of evidence-based chronic disease prevention interventions: a quantitative study in Shanghai, China

Abstract: Background: Epidemic chronic diseases pose significant challenges to the improvement of healthcare in China and worldwide. Despite increasing international calls for the inclusion of evidence-based decision-making (EBDM) processes in chronic disease prevention and control programming as well as policymaking, there is relatively little research that assesses the current capacity of physicians and the factors that influence that capacity in China. Method: This cross-sectional study was conducted in community hea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…However, they did not appear to be confident in their abilities to implement them in practice ( Table 1 ). This may be linked to their perceived difficulty in locating appropriate resources, including Cochrane resources ( Table 2 ) and a lack of experience, which aligns with previous studies [ 7 , 8 , 10 , [12] , [13] , [14] ]. The findings suggest that healthcare providers and scholars require more support regarding the availability of evidence resources, including Cochrane resources, and in improving the competency of finding and using evidence resources.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…However, they did not appear to be confident in their abilities to implement them in practice ( Table 1 ). This may be linked to their perceived difficulty in locating appropriate resources, including Cochrane resources ( Table 2 ) and a lack of experience, which aligns with previous studies [ 7 , 8 , 10 , [12] , [13] , [14] ]. The findings suggest that healthcare providers and scholars require more support regarding the availability of evidence resources, including Cochrane resources, and in improving the competency of finding and using evidence resources.…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, many frontline clinicians have exhibited a positive attitude towards evidence-based healthcare and agree that its implementation is necessary in clinical environments [ [7] , [8] , [9] ]. However, previous studies have also suggested that clinicians in China possess a low to moderate level of evidence-based practice competency [ 7 , [10] , [11] , [12] ], as well as limited experience in applying new knowledge and practicing knowledge translation [ 8 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire was adapted from a study comparing the use of EBCDP processes ( 17 , 18 ). At the beginning of the questionnaire, we explained the purpose of the questionnaire and relevant concepts to the respondents (EBCDP, evidence-based programs, etc.).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, controlling and preventing chronic diseases have become the main focus of health systems [ 10 ]. To achieve the best possible outcomes, evidence-based chronic disease prevention (EBCDP) emerged as a new approach to developing evidence-based programs to ensure that healthcare providers have access to up-to-date scientific evidence regarding chronic diseases [ 11 ]. Despite all efforts, there is a gap between knowledge generation and evidence implementation due to the inability of clinicians to search for and evaluate evidence [ 12 ].…”
Section: Introductionmentioning
confidence: 99%